Evolution in the Landscape of Deceptive Practices in the Banking Sector: A Perspective on the Indian Scenario" (International Journal of Food and Nutritional Sciences, 2022)
The evolution in the landscape of deceptive practices in India signifies a dynamic shift in the realm of fraudulent activities. As the socio-economic fabric transforms and technological advancements continue to shape the business environment, the methods employed by individuals engaging in deceptive practices have also undergone significant changes. This transformation not only reflects the adaptability of those involved in fraudulent activities but also poses new challenges for regulatory bodies and law enforcement agencies. Understanding this evolving landscape is crucial for devising effective strategies to combat fraud and safeguard the integrity of various sectors in the Indian context. This introduction sets the stage for a comprehensive exploration of the current state of deceptive practices, shedding light on the emerging trends and their implications for the broader framework of governance and security in the country.